2013
DOI: 10.3109/08958378.2013.800618
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic toxicity and carcinogenicity studies of 1,2-dichloropropane inhalation to mice

Abstract: The subchronic toxicity and carcinogenicity of 1,2-dichloropropane (DCP) in male and female B6D2F1 mice exposed to DCP by inhalation for 13 weeks or for 2 years was investigated. The DCP concentrations used were 50, 100, 200, 300 or 400 ppm (v/v) in the 13-week study, and 32, 80 or 200 ppm (v/v) in the 2-year study. Thirteen weeks inhalation exposure of mice to DCP caused death in the mice exposed to 300 ppm and above, and was found to induce hemolytic anemia and lesions of the liver, forestomach and heart. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Two animal experiments had found that inhalation exposure to 1,2-DCP increases the incidence of bronchioloalveolar tumours in mice and that of nasal cavity tumours in rats, although no bile duct tumour development was observed in either species 16 17. It is unclear why the region of tumour development differs between humans and rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Two animal experiments had found that inhalation exposure to 1,2-DCP increases the incidence of bronchioloalveolar tumours in mice and that of nasal cavity tumours in rats, although no bile duct tumour development was observed in either species 16 17. It is unclear why the region of tumour development differs between humans and rodents.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some in vivo experiments showed that 1,2-DCP-exposed mice developed malignant lung and hepatocellular tumours, suggesting the carcinogenicity of 1,2-DCP and/or its metabolites78. In the liver, a major organ in the metabolism of various compounds, xenobiotics are generally converted to the hydrophilic form by Phase I (oxidation) and Phase II (conjugation) reactions, and are subsequently excreted into the extracellular space by the Phase III (elimination) system9 such as ATP-binding cassette sub-family C member 2 (ABCC2) and ABCG2.…”
mentioning
confidence: 99%
“…A recent report showed that inhalation of the solvent in mice and rats increased the incidence of Harderian gland adenoma and nasal cavity tumor, respectively 4,5) . By gavage administration, 1,2-DCP induced hepatocellular adenomas in mice but not in rats 6) .…”
mentioning
confidence: 99%